Role of Handicrafts in Self-employment & Economic Prosperity of Women: A Study on Jamalpur Pouroshava (Journal of Green Business School, 2025)
Handicrafts (hand stitch) industry of Bangladesh has a great potential in economic development of the country. Although the handicrafts sector is the most decentralized and unorganized sector of the Bangladesh economy but this sector plays a major role in the economic development to the nation. The main objectives of the study are investigating the role of handicrafts (hand stitch) industry in self-employment of women and specific objectives are knowing the economic conditions of handicrafts workers, relationship with economic growth and recommendation for policy making for developing handicraft industry in Bangladesh. Quantitative method is used for the study and data are collected through structural interviews from the respondents. The study found that most of women who are engaged in handicraft work and business, they belong to less education status and their family income status is low, they also have changed their socio-economics status but that is not sufficient at present world like other developing countries. We need to effective policy for their development.J. of Green Business. Sch. Vol 6(1), Jan-Dec, 2023; pp 69-82